ASSESSMENT IN TRANSLANGUAGING CLASSROOMS: INDONESIAN UNIVERSITY ENGLISH TEACHERS' EXPERIENCES AND RECOMMENDATIONS - Hapsari, Yulia; Hamied, Fuad Abdul; Emilia, Emi (University of Kuningan, 2025)
Translanguaging has increasingly been used in English classrooms to symbolize a movement away from native-speakerism in the growing multilingual society. In translanguaging classroom contexts, students are evaluated on their ability to use their whole language repertoire to express what they know and can do in classroom tasks. Four principles of translanguaging in assessment are provided as guidelines. However, many classroom translanguaging studies barely address how the four principles are employed. This study explores teachers’ experiences in performing assessments in classroom translanguaging in relation to the four principles of translanguaging assessment to propose recommendations for translanguaging classrooms at the university level. Classroom observations and interviews were conducted with five teachers of an English department at a university in Indonesia. A thematic analysis performed on the data demonstrated that the teachers’ assessments had accommodated the different voices in assessment, the use of other people and other resources, and the authenticity of the tasks. However, the distinction between general linguistic and language-specific performances was not carried out. Another theme emerged – shared language among interlocutors. Recommendations covering improving teachers’ knowledge about pedagogical translanguaging, how to design translanguaging assessments, and how to manage the assessment are made to facilitate good alignment between classroom translanguaging instructions and assessments to maximize students’ learning benefits.